ANALISIS HARGA POKOK PENJUALAN DAN FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI USAHATANI UBI KAYU DI KABUPATEN LAMPUNG TENGAH - Rohayani Rohayani; Raden Hanung Ismono; Rabiatul Adawiyah (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2021)
The objectives of this research are to find out the selling standard cost of cassava production and the factors that influence the production of cassava farming. The research was a survey conducted in Central Lampung Regency in October-November 2018. The samples are 73 cassava farmers selected randomly. Data were analyzed using total income, total costs, profit margin, and Cobb-Douglas production function. The results showed that selling standard cost with profit margin of 13 percent is IDR1,145.81 in Terusan Nunyai Subsdistrict and IDR1,032.59 in Bandar Mataram Subsdistrict. The average price received by farmers is IDR1,456.57 and IDR1,570.65 respectively. It means that farmers have benefit from technical efficiency of cassava farming. There is a significant difference between the selling cost of cassava in area close to factory and that in farther area. The factors that affect the production of cassava are seeds, urea fertilizer, and location.Key words: Cassava, determining production cost, determining selling cost, farming.